49. Combined treatments with Hadrontherapy – in vitro tests and preclinical approach. (December 2018) - Russo, G.; Pisciotta, P.; Marchese, V.; Cammarata, F.P.; Minafra, L.; Forte, G.I.; Bravatà, V.; Cirrone, G.A.P.; Fallacara, A.L.; Maccari, L.; Torrisi, F.; Calabrese, G.; et al.
Abstract : Purpose: Glioblastoma multiforme (GBM) is the most aggressive types of central nervous system tumors. The aim of the project is to validate an innovative molecule developed by Lead Discovery Siena [LDS] showing inhibitory activity against Src kinases to be associated with proton therapy treatments. Materials: Human glioblastoma cells (U87) were treated at INFN-LNS in Catania with 2 and 10 Gy of proton beams at dose rate of 10 Gy/min in the middle of the extended modulated Bragg peak and in combination with different concentrations of the LDS molecule (10 and 20 μM). The fraction of surviving cells (SF) was evaluated with the clonogenicity test 15 days after irradiation. Results: The data in the figure show the synergistic effect of the combined treatment with LDS. Conclusions: In vitro studies confirmed the efficacy of the hadron therapy treatment in combination with the molecule. The next step is to translate these studies on the mouse model thanks to the existence of an Animal Facility created by the synergy between the following institution: the LNS-INFN, the University of Catania – Capir Center, IBFM-CNR and H. Cannizzaro, with the departments of Nuclear Medicine and Medical Physics. The facility will be able to provide unique research activities in the European panorama: hadron therapy treatments, dose distribution studies using the Monte Carlo GEANT4 method, molecular imaging using microPET/ CT tomography with different radiotracers and image processing implementation for therapy response quantification.